Early abdominal aortic graft infection due to Propionibacterium acnes: a case report and review of the literature. (3rd April 2018) - Pallotto, Carlo; Simonte, Gioele; Verzini, Fabio; Lenti, Massimo; Baldelli, Franco; Francisci, Daniela; Fiorio, Maurizio
Abstract : Propionibacterium acnes is a member of the human microbiota that has been recently associated with late-onset infections of indwelling devices, especially shoulder prosthesis. Aortic graft infection are rare events with significant morbidity and mortality. Here, we describe the case of an abdominal aortic graft infection due to P. acnes with an unusual early onset. A review of the recent English language literature has been added.